Cardiovascular disease risk in women (Evaluation of risk factors for ischaemic heart disease in group of 6 310 women from Pomerania Region) - Karwat, Błażej; Chomicz, Janusz; Gorący, Jarosław; Pieczul-Mróz, Joanna; Przybycień, Krzysztof; Kornacewicz-Jach, Zdzisława (Menopause Review/Przegląd Menopauzalny, 2003)
In United States Of America ischaemic heart disease is the main death cause of women aged over 50 and third cause of death in all women population. Similar rates become actual for Europe. The aim of our study is evaluation of risk factors prevalence for ischaemic heart disease in population of women at aged 50 years from Pomerania Region. 6 310 women born in the year 1951 were included to study. Based on collected data according to recommendations of Polish Cardiologic Society, risk level for cardiovascular diseases was estimated. In 50% of women from study group high and very high risk for ischeemic herat disease was noted. In 26% of them obesity, in 50% elevated total cholesterol and elevated LDL level were noted and 33% have hypertension. 60% of women were smokers.